Extremely rapid development of transurethral resection of the prostate syndrome - Lađević Nebojša; Likić-Lađević Ivana; Durutović Otaš; Nale Đorđe; Džamić Zoran (Vojnosanitetski Pregled)
Background. The transurethral resection of the prostate (TURP) syndrome is reported after ureteroscopic procedures with irrigating solutions. TURP syndrome may occur quickly or up to 24 hours postoperatively. TURP syndrome affects many systems and manifests itself mainly through acute changes in intravascular volume and plasma solute concentrations. Case report. We reported a 72- year-old patient with benign prostatic hyperplasia, diabetes mellitus and angina pectoris who underwent TURP under spinal anesthesia. Unusual marked somnolence, bradycardia (38 beats/min), disorientation and face edema indicated a diagnosis of TURP syndrome only 15 minutes after the operation had started. The diagnosis confirmed by arterial gas analyses (metabolic acidosis, pH was 7.29) and hyponatremia (96 mmol/l). Aggressive and adequate therapy with diuretic and bicarbonates decreased symptoms and saved patient's life. Conclusion. Very fast development of TURP syndrome is possible. Continuous patient monitoring is necessary to provide fast recognition of TURP syndrome. Adequate therapy can prevent considerable complications.